Fabrication and characterization of cinnamaldehyde loaded polysaccharide composite nanofiber film as potential antimicrobial packaging material. (December 2020) - Yang, Yufan; Zheng, Shengliang; Liu, Qian; Kong, Baohua; Wang, Hao
Graphical abstract: Highlights: The cinnamaldehyde was successfully encapsulated into pullulan/ethyl cellulose nanofiber films. The composite nanofiber films exhibited hydrophobic surface, improved flexibility, and strong antimicrobial activity. The composite nanofiber films have potential as active antimicrobial packaging materials. Abstract: In this study, the pullulan/ethyl cellulose-cinnamaldehyde (CA) composite nanofiber films were fabricated via the electrospinning technique. The scanning electron microscopy observation showed that the CA loaded nanofiber films possessed homogenous morphologies, and the average diameter of fibers ranged from 231.9–203.4 nm. The Fourier transform infrared spectroscopy analysis confirmed that the CA was successfully loaded in the nanofiber films. The water contact angle test suggested that the incorporation of CA at a certain concentration improved the surface hydrophobicity of nanofiber films. The mechanical test showed that the addition of CA increased the flexibility of nanofiber films. Besides, the antibacterial assays indicated that the CA loaded nanofiber films could effectively inhibit the growth of both Gram-negative ( E. coli ) and Gram-positive ( S. aureus ) bacteria. This work suggested the potential of the pullulan/ethyl cellulose-CA composite nanofiber films as a desirable material for active food packaging applications.